Status of Rice False Smut Disease in Natore District of Bangladesh - Sarker, MM; Haque, AHMM; Nessa, B; Salam, MU; Islam, MM; Muqit, A (Bangladesh Rice Journal, 2017)
Rice false smut has become an emerging disease across the world. Its incidence has become serious in Bangladesh during T. Aman season in the last five years. However, the status of the disease in farmers field has not been estimated in this country. This study included a survey of 90 fields in four unions of Natore district during ripening stage of T. Aman rice of 2015 in order to estimate the disease incidence, number of smut balls per infected panicle and yield loss, and to ascertain effectiveness of farmers unregistered foliar fungicide application. The results show that across the fields, disease incidence, number of smut balls per infected panicle and yield loss were 8.06±2.02%, 2.88±0.17 and 0.72±0.18% (± is 95% confidence interval), respectively. Disease incidence (18.71±5.18%), number of smut balls per infected panicle (3.51±0.39) and yield loss (1.75±0.38%) was the highest in Ramananda Khajura union compared to the other three unions surveyed. Among the varieties, BRRI dhan49 incurred the highest disease incidence (18.71±5.18%). The number of smut balls per infected panicle (3.51±0.39) and yield loss (1.75±0.38%) were also the highest in this variety. The crops which flowered during mid October to early November showed significantly higher disease incidence than early flowering crops. Application of unregistered foliar fungicides tended to have reduced the disease, but did not show significant difference with no fungicide application. It is concluded that the strategic management of the disease may be directed to the specific areas of the fields where there is a history of the disease through manipulating genotypes and transplanting time. Farmers should be cautious on adopting chemical option as there is no registered fungicide yet in Bangladesh for tactical management of the disease. Bangladesh Rice j. 2016, 20(2): 31-37